TABOO LANGUAGE IN MALAY PANAI LANGUAGE OF LABUHAN BILIK DIALECT - Hilman Haidir; Mulyadi Mulyadi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
This research dealt with the identification of taboo language in Malay Panai Language of Labuhan Bilik Dialect. It is a language spoken by people living in Labuhan Bilik village, Panai Tengah district, Labuhan Batu, Rantau Prapat. The objective of this research was to describe the classification of the taboo words in Malay Panai Language of Labuhan Bilik Dialect (MPLLBD). The research applied was descriptive qualitative approach. The data were collected through observation, recording, and field notes. Then, the data were analyzed by identifying taboo words and categorizing them into the types of taboo words. Thus, each of the taboo words were presented in some examples of utterances in the language. Some words were considered taboo or not depending on the context in which they were used. The finding shows that taboo words in MPLLBD could be either implicit or explicit. In conclusion, there were some classifications of taboo words in the language which were related to the utterances of sex, death, excretion, body function, religion, animals, vague words, and disease.